Religious coping, religiosity, depressive and anxiety symptoms among Malaysian medical students / Benedict Francis - Benedict , Francis (2019)
Medical students are vulnerable to depression and anxiety due to the nature of their academic life. Religious coping is often used as a coping mechanism in this population. This study aimed to determine the prevalence of depressive and anxiety symptoms among medical students as well as to determine the correlation between religious coping, religiosity and socio-demographic factors with anxiety and depression. A cross sectional design was used for this study and samples were collected via convenient sampling. Religiosity and religious coping were measured using the Malay version of the Duke Religious Index (DUREL-M) and the Malay version of the Brief Religious Coping Scale (Brief RCOPE). Depression and anxiety were measured using the Malay version Hospital and Anxiety Depression Scale (HADS-M). All scales used were validated for the Malaysian population. A total of 622 patients participated in this study. A majority of them were female, single and from the Muslim and Buddhist religion. They scored moderately on the organized (mean: 3.51) and non-organized religious (mean: 3.85) subscales of the DUREL, but had high intrinsic religiosity (mean: 12.18). The prevalence of anxiety and depressive symptoms were 4.7 % and 17.4 % respectively. Islam, negative religious coping and the presence of depressive symptoms were significantly associated with anxiety symptoms. Only the presence of anxiety symptoms was significantly associated with depressive symptoms. The prevalence of depressive and anxiety symptoms among Malaysian students were lower than previous local and international data. They had high intrinsic religiosity however negative religious coping was associated with increased anxiety symptoms. Focus needs to be directed towards reducing negative religious coping as it has adverse impact on the mental health of Malaysian medical students